MP23: Giving medical students what they deserve - a rigorous, equitable and defensible CaRMS selection process. (May 2019) - Paterson, Q.; Hartmann, R.; Woods, R.; Martin, L.; Thoma, B.
Abstract : Innovation Concept : The fairness of the Canadian Residency Matching Service (CaRMS) selection process has been called into question by rising rates of unmatched medical students and reports of bias and subjectivity. We outline how the University of Saskatchewan Royal College emergency medicine program evaluates CaRMS applications in a standardized, rigorous, equitable and defensible manner.Methods : Our CaRMS applicant evaluation methods were first utilized in the 2017 CaRMS cycle, based on published Best Practices, and have been refined yearly to ensure validity, standardization, defensibility, rigour, and to improve the speed and flow of data processing. To determine the reliability of the total application scores for each rater, single measures intraclass correlation coefficients (ICCs) were calculated using a random effects model in 2017 and 2018.Curriculum, Tool or Material : A secure, online spreadsheet was created that includes applicant names, reviewer assignments, data entry boxes, and formulas. Each file reviewer entered data in a dedicated sheet within the document. Each application was reviewed by two staff physicians and two to four residents. File reviewers used a standardized, criterion-based scoring rubric for each application component. The file score for each reviewer-applicant pair was converted into a z-score based on each reviewer's distribution of scores. Z-scores of all reviewers for a single applicant were then combined by weighted average, with the group of staff and group of residents each being weighted to represent half of the final file score. The ICC for the total raw scores improved from 0.38 (poor) in 2017 to 0.52 (moderate) in 2018. The data from each reviewer was amalgamated into a master sheet where applicants were sorted by final file score and heat-mapped to offer a visual aid regarding differences in ratings.Conclusion : Our innovation uses heat-mapped and formula-populated spreadsheets, scoring rubrics, and z-scores to normalize variation in scoring trends between reviewers. We believe this approach provides a rigorous, defensible, and reproducible process by which Canadian residency programs can appraise applicants and create a rank order list.